Assessment of Cardiometabolic Risk Factors in Viral Liver Cirrhosis - Soliyeva, Kamola (GLOBAL SCIENTIFIC CONFERENCE ON MULTIDISCIPLINARY RESEARCH, 2026)
Chronic hepatic fibrogenesis induced by hepatotropic viruses fundamentally disrupts systemic metabolic homeostasis, yet the precise trajectory of cardiovascular complications in these patients remains under-investigated due to the clinical masking of traditional risk parameters. This cross-sectional observational study quantifies the prevalence and severity of cardiometabolic risk factors among patients diagnosed with viral liver cirrhosis, specifically focusing on insulin resistance, silent atherosclerosis, and the lipid paradox inherent to synthetic hepatic dysfunction. The investigation evaluated a cohort of 115 patients with compensated and subcompensated viral cirrhosis (Child-Pugh classes A and B) alongside a matched normative control group of 50 healthy individuals. Diagnostic protocols integrated high-resolution B-mode ultrasonography to measure carotid intima-media thickness (cIMT), calculation of the Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), and the Atherogenic Index of Plasma (AIP). Empirical data indicated a severe dissociation between standard lipid profiles and actual vascular health; despite ostensibly normal or reduced total cholesterol levels, 68% of the cirrhotic cohort exhibited aggressive metabolic dysfunction. The mean HOMA-IR in the viral cirrhosis group escalated to 4.2 ± 0.6 compared to 1.8 ± 0.4 in controls (p < 0.01). Similarly, structural vascular remodeling was highly prevalent, with the average cIMT measuring 1.15 ± 0.12 mm in patients with Hepatitis C-induced cirrhosis, significantly correlating with elevated high-sensitivity C-reactive protein (hs-CRP) levels. Chronic viral hepatitis driving cirrhotic transformation acts as an independent systemic atherogenic catalyst. Standard cardiovascular risk calculators systemically underestimate morbidity in this demographic, dictating an absolute clinical necessity to integrate non-traditional metabolic markers like AIP and routine carotid ultrasonography into standard hepatology monitoring protocols to prevent silent cardiovascular mortality.